PENERAPAN DATA MINING ASOSIASI PADA PERSEDIAAN OBAT - Febrivani, Elischa; Saifullah; Winanjaya, Riki (Jurnal Ilmu Komputer dan Sistem Informasi (JIKOMSI), 2021)
Drug stock shortages or vacancies at a hospital will have a very bad impact on the success and smoothness of drug delivery transactions, the cause of a drug stock vacancy is the absence of information conveyed from the pharmaceutical installation to the supplier of the drug supplier. To prevent this, we need a system that can help suppliers of goods in order to know about the availability of drugs in pharmaceutical installations. Based on drug transaction data, this system is built using the Association method with Apriori algorithm which is a technique in data mining to find associative rules of combination between itemset. The calculation is done by determining support and confidence that will result in association rules, which can be used to determine what drug stocks are needed to prevent a drug stock gap.